ANALISIS PERSEDIAAN BAHAN BAKU PADA AGROINDUSTRI KRIPIK BUAH SANUR DI KABUPATEN MALANG - Nineng Puspito Ratih; Anik Suwandari; M Rondhi (Jurnal Sosial Ekonomi Pertanian (J-SEP), 2017)
Various fruits can be tranformed into delicious edible foods like chips. That was a basic idea which inspired “Sanur” Fruit Chips Agroinduntry to make chips which based on fruits processing. This agroindustry still performs traditional methods to manage its fruit inventory as raw material. This lead to a fluctuation and uncertainty in inventory stock. The traditional inventory in this agroindustry also caused a bottleneck in production process. The research was aimed to : (1) determine the economic order quantity of fruit chips agroindustry. (2) determine the most efficient re-order point of inventory in “Sanur” Fruit Chips Agroindustry. The research was descriptive and analytical. The key informant was selected purposively based on some criteria. Data was collected by using interview and observation. The result showed that : (1) economic order quantity was more preferable than Lot for Lot and tradional methods. (2) the traditional re-order point method in “Sanur” fruit chips agroindustry was not efficient. It was indicated by the safety stock, the amount of procurement and the inventory of minimum raw materials which showed full uncertain.